Aging specifically impairs switching to an allocentric navigational strategy - Harris, Mathew A.; Wiener, Jan M.; Wolbers, Thomas (Frontiers in Aging Neuroscience, 2012)
Navigation abilities decline with age, partly due to deficits in numerous component processes. Impaired switching between these various processes (i.e. switching navigational strategies) is also likely to contribute to age-related navigational impairments. We tested young and old participants on a virtual plus maze task, expecting older participants to exhibit a specific strategy switching deficit, despite unimpaired learning of allocentric (place) and egocentric (response) strategies following reversals within each strategy. Our initial results suggested that older participants performed worse during place trial blocks but not response trial blocks, as well as in trial blocks following a strategy switch but not those following a reversal. However, we then separated trial blocks by both strategy and change type, revealing that these initial results were due to a more specific deficit in switching to the place strategy. Place reversals and switches to response, as well as response reversals, were unaffected. We argue that this specific ‘switch-to-place' deficit could account for apparent impairments in both navigational strategy switching and allocentric processing, and contributes more generally to age-related decline in navigation.